2015
DOI: 10.3762/bjoc.11.161
|View full text |Cite
|
Sign up to set email alerts
|

Tandem cross enyne metathesis (CEYM)–intramolecular Diels–Alder reaction (IMDAR). An easy entry to linear bicyclic scaffolds

Abstract: SummaryA new tandem cross enyne metathesis (CEYM)–intramolecular Diels–Alder reaction (IMDAR) has been carried out. It involves conjugated ketones, esters or amides bearing a remote olefin and aromatic alkynes as the starting materials. The overall process enables the preparation of a small family of linear bicyclic scaffolds in a very simple manner with moderate to good levels of diastereoselectivity. This methodology constitutes one of the few examples that employ olefins differently than ethylene in tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…A second parameter to consider is the effect of the presence of additives. Indeed, it has been demonstrated that the addition of several molecules during the metathesis reaction (such as acetic acid, benzoquinones, or thioureas) [22][23][24] positively affect the final catalytic properties of the organometallic compound. Different additives could result in completely different active species from the same Grubbs catalyst and trigger different catalytic pathways to produce structurally unique products.…”
Section: Activity Of Soluble Hoveyda-grubbs Second-generation Catalysmentioning
confidence: 99%
“…A second parameter to consider is the effect of the presence of additives. Indeed, it has been demonstrated that the addition of several molecules during the metathesis reaction (such as acetic acid, benzoquinones, or thioureas) [22][23][24] positively affect the final catalytic properties of the organometallic compound. Different additives could result in completely different active species from the same Grubbs catalyst and trigger different catalytic pathways to produce structurally unique products.…”
Section: Activity Of Soluble Hoveyda-grubbs Second-generation Catalysmentioning
confidence: 99%
“…In 2015, Fustero’s group has reported a tandem CEM and intramolecular DA reaction methodology for the generation of linear bicyclic ketone, lactone, and lactam scaffolds in a simple manner with good diastereoselectivity (Scheme 30). 23 In this regard, various conjugated ketones, esters, and amides bearing an alkene moiety 113 were reacted with different aromatic alkynes 114 in the presence of HG-II catalyst to obtain the bicyclic ketone, lactones, and lactams 115 . The resulting bicyclic heterocycles 115 were formed via tandem CEM and an intramolecular DA reaction sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Synthèse de tris-fullérodendrimères de type Janus par une combinaison « métathèse croisée d'oléfinesaldolisation ».Nous aimerions également appliquer une réaction tandem métathèse croisée d'enyne/Diels-Alder décrite dans la litérature81,82 pour préparer des tris-fullérodendrimères comportant trois mésogènes différents (schéma 21). La synthèse débute par la réaction de métathèse croisée d'enyne entre une oléfine de type I et un alcyne terminal pour donner l'intermédaire diènique.Ce diène est par la suite mis en jeu dans la réaction de Diels-Alder avec un diénophile pour conduire au produit désiré.…”
unclassified